From buzz to bust: How fake news shapes the business cycle - Tiziana Assenza; Fabrice Collard; Patrick Fève; Stefanie J. Huber (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
The threats that misinformation poses to politics and public health are well documented, but the macroeconomic effects of fake news remain largely unexplored. This column highlights insights from recent research on the impact of fake news on economic stability. Leveraging a novel dataset, our study unveils the detrimental effects of technology-related fake news on key economic indicators. Fake news profoundly influences economic dynamics, from heightened uncertainty to amplified business cycle fluctuations. Moreover, nuanced differences in the economic response to various types of fake news underscore the complexity of the challenge. As policymakers grapple with the ramifications of fake news, our research suggests that they should pay attention to its effects on economic stability.
Keywords: 330